"The walls came down:" A Mixed-Methods Multi-Site Prison Arts Program Evaluation. (3rd July 2021) - Littman, Danielle Maude; Sliva, Shannon M
Abstract: Considerable research has linked participation in arts programs to a constellation of positive social emotional outcomes for incarcerated participants. This article describes and evaluates a set of semester-long University of Denver Prison Arts Initiative (DU PAI) workshops. Through a pretest-posttest evaluation design inclusive of 22 quantitative and three qualitative items, we measured a range of outcomes for DU PAI participants (N = 119). Quantitative findings support prior work which associates participation in prison arts programs with social emotional outcomes such as community connection, skill attainment, and self-efficacy. Qualitative findings offered insight into participants' experiences of the workshops, including: learning, growth, and discovery; opening up; authentic self-expression; empathy and perspective taking; belonging and connection; creative collaboration; joy and freedom. We also identified facilitator qualities which foster participant growth, including: safety, caring and respect, participation, and emotional involvement. Our findings suggest that prison arts programming may transcend skills-based and social emotional outcomes to invoke liberatory experiences for participants. There is a need for additional research to more clearly explore the effects of contextual factors and further concretize the unique role of arts programs in carceral spaces.